(untitled) (Baghdad Science Journal, 2016)
This study was conducted to determine the activity of plant Sesbania rostrata and two isolate from arbuscular mycorrhizae fungi (A,B) as a bioremediation of soil polluted by cadmium and lead elements in north and south of Baghdad city. The results showed that the average of soil pollution by cadmium and lead elements in north of Baghdad was less than the average of soil pollution in the south of Baghdad which recorded 10.0, 9.0 mg/kg and 27.0, 25.0 mg/kg respectively. The plant Sesbania recorded ability to accumulate the lead element in shoot system 19.65 mg/kg and in root system 27.2 mg/kg and for cadmium element 19.6, 24.6 mg/kg in shoot and root respectively. The results showed that the isolate A from soil pollution is more effected than isolate B which isolated from uncontaminated soil.